2010
DOI: 10.1093/geront/gnq050
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nursing Home Placement in Alzheimer's Disease: A Longitudinal Study of Cognition, ADL, Service Utilization, and Cholinesterase Inhibitor Treatment

Abstract: The rate of functional but not cognitive decline was a strong risk factor for NHP. The results could be used to identify the care recipients that might risk early NHP to ensure that these individuals receive a sufficient level of assistance. Furthermore, higher doses of ChEI might postpone institutionalization in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 31 publications
9
102
2
Order By: Relevance
“…The reduced risk of nursing home placement in this study contradicts the findings by Wattmo et al [24], who aimed to identify risk factors for nursing home placement. Among other predictors, they found that solitary living was a significant risk factor for nursing home placement.…”
Section: Discussioncontrasting
confidence: 99%
“…The reduced risk of nursing home placement in this study contradicts the findings by Wattmo et al [24], who aimed to identify risk factors for nursing home placement. Among other predictors, they found that solitary living was a significant risk factor for nursing home placement.…”
Section: Discussioncontrasting
confidence: 99%
“…The SATS is a prospective, open-label, observational, nonrandomized, multicenter study that has been described in several publications [18,19,20,21]. In total, 1,258 participants were recruited until April 2008 by 14 memory clinics that cover different parts of Sweden.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, the risk of such events is clearly dose dependent (as seems to be the case for efficacy), and this was shown, at least for donepezil and rivastigmine, in a meta-analysis of randomized clinical trials [Ritchie et al 2004]. The clinical benefit of reaching higher doses from a QoL perspective is supported by a large 3-year, prospective, observational study of 880 patients with AD treated with CIs, in which a higher dose of CIs (donepezil >6.9 mg/ day, oral rivastigmine >6 mg/day, galantamine >16 mg/day) was independently associated with a lower institutionalization risk [Wattmo et al 2011]. The risk of gastrointestinal side effects leading to treatment withdrawal is particularly high for the oral formulation of rivastigmine, both in clinical trials [Birks et al 2009] and in clinical practice [Mossello et al 2004].…”
Section: Adverse Events Risk Versus Efficacymentioning
confidence: 99%